2018
DOI: 10.3847/1538-4357/aaa3fd
|View full text |Cite
|
Sign up to set email alerts
|

A Dependence of the Tidal Disruption Event Rate on Global Stellar Surface Mass Density and Stellar Velocity Dispersion

Abstract: The rate of tidal disruption events (TDEs), R TDE , is predicted to depend on stellar conditions near the super-massive black hole (SMBH), which are on difficult-to-measure sub-parsec scales. We test whether R TDE depends on kpcscale global galaxy properties, which are observable. We concentrate on stellar surface mass density,  S M , and velocity dispersion, s v , which correlate with the stellar density and velocity dispersion of the stars around the SMBH. We consider 35 TDE candidates, with and without kno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 116 publications
7
87
1
Order By: Relevance
“…We find an excellent fit with a Sérsic index of only 0.7 (Figure 15), indicating a less sharply-peaked light distribution than typical TDE hosts. Graur et al (2018) showed that TDE hosts generally have a stellar mass surface density log(Σ M * /(M kpc −2 )) > 9, which is consistent with typical quiescent galaxies, but high for star-forming TDE hosts. This can be interpreted as evidence for a high density of stars around the central SMBH, which could naturally lead to a higher rate of TDEs (Graur et al 2018), as earlier proposed by Stone & van Velzen 2016).…”
Section: Host Galaxymentioning
confidence: 64%
See 2 more Smart Citations
“…We find an excellent fit with a Sérsic index of only 0.7 (Figure 15), indicating a less sharply-peaked light distribution than typical TDE hosts. Graur et al (2018) showed that TDE hosts generally have a stellar mass surface density log(Σ M * /(M kpc −2 )) > 9, which is consistent with typical quiescent galaxies, but high for star-forming TDE hosts. This can be interpreted as evidence for a high density of stars around the central SMBH, which could naturally lead to a higher rate of TDEs (Graur et al 2018), as earlier proposed by Stone & van Velzen 2016).…”
Section: Host Galaxymentioning
confidence: 64%
“…We also detect narrow absorption lines from the host galaxy, from which we measure the redshift z = 0.1089± 0.0005. The host is a Balmer-strong absorption galaxy -a rare type of galaxy that is greatly over-represented among TDE hosts (Arcavi et al 2014;French et al 2016;Law-Smith et al 2017;Graur et al 2018).…”
Section: Discovery and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent analysis (Graur et al 2018) of a larger TDE host sample found somewhat smaller but still significant rate enhancements (R = 35 +21 −17 and R = 18 +8 −7 for the same categories of Balmer-line strength). The Graur et al (2018) rate enhancements were computed from a larger but more heterogeneous sample of 33 TDE host galaxies, and vary significantly if one examines different sub-samples. TDE host galaxies display some other peculiarities as well, such as an unusually high surface brightness on ∼ kpc scales (Law-Smith et al 2017b).…”
Section: Observationally Inferred Ratesmentioning
confidence: 83%
“…(3) We convolve P (r, ∆t) with Eq (20) In Figure 2 we place contours of P (∆t) for ∆t = 1yr (blue dotted contours) and ∆t = 5yr (red dot-dashed contours), respectively, on the two-dimensional parameter plane of (η, σ/v c ). The two black contours are the current observational constraint of N tde = 10 5 − 10 6 per PSB, corresponding to 10 −4 − 10 −3 yr −1 per PSB with a time span of 1Gyr (French et al 2016) [also see Law-Smith et al (2017); Graur et al (2018)]. Also shown as horizontal magenta dot-dashed line is an indicative case where the vertical velocity dispersion is equal to sound speed of atomic cooling gas gas of temperature 10 4 K, out of which stars in the disk may have formed.…”
Section: Tde Repeatersmentioning
confidence: 99%